Prevalence of depression in older people with hip fracture: A systematic review and meta-analysis. (February 2021) - Heidari, Mohammad Eghbal; Naghibi Irvani, Seyed Sina; Dalvand, Pegah; Khadem, Mohaddeseh; Eskandari, Fereshte; Torabi, Fatemeh; Shahsavari, Hooman
Abstract: Introduction: Hip fracture disrupts general health and is one of the most common physical injuries in the elderly. Depression is the most common mood disorder in older people and one of the main complications of hip fractures. Aim and methods: We conducted a meta-analysis to estimate the prevalence of depression in older people with hip fractures. Relevant literature published until July 2019 was obtained and screened according to established inclusion criteria. Two researchers independently carried out quality assessment and data extraction before the meta-analysis. We calculated proportions with 95% confidence intervals (CI). To investigate the sources of heterogeneity, we performed subgroup analyses based on study design, follow-up duration, type of fracture, and gender. Results: Twenty-seven studies with a combined sample size of 11958 were included. The overall prevalence of depression in older people with hip fracture was 23% (95% CI: 0.18 to 0.29). The lowest and highest prevalence of depression was in Asia (0.19) and America (0.27) respectively. Conclusion: In this systematic review and meta-analysis the estimated prevalence of depression among older hip fracture patients was 23%. Further research is needed to identify strategies for preventing and treating mood disorders in this population.